Community Understanding of 13 General Messages of Balanced Nutrition (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Indonesia still faces a double burden of nutritional problems, especially in children. It is essential to promote balanced nutrition education to mothers of toddler years old. They are more familiar with â€œ4 Healthy and 5 Completeâ€ which has been replaced by â€œBalanced Nutrition Guidelinesâ€ (PUGS). This cross-sectional study aimed to assess the knowledge of mothers about 13 PUGS messages in East Lombok District. This study was conducted using quantitative approach and supported with qualitative data. Data was collected by interviewing 188 mothers, stakeholders, health workers, cadres and community leaders. Data was analyzed using logistic regression to determine which messages are correlated to nutritional status. The result shows that the majority of mothers do not understand PUGS. There is a relationship between motherâ€™s knowledge with childrenâ€™s nutritional status. Motherâ€™s knowledge of consuming iron-containing foods, drinking clean and sufficient water are associated with childrenâ€™s nutrition status. PUGS messages are better understood by health workers compared to mothers.